Uncovering the salt response of soybean by unraveling its wild and cultivated functional genomes using tag sequencing. - Zulfiqar Ali (Public Library of Science (PLoS), 2012)
Soil salinity has very adverse effects on growth and yield of crop plants. Several salt tolerant wild accessions and cultivars are reported in soybean. Functional genomes of salt tolerant Glycine soja and a salt sensitive genotype of Glycine max were investigated to understand the mechanism of salt tolerance in soybean. For this purpose, four libraries were constructed for Tag sequencing on Illumina platform. We identify around 490 salt responsive genes which included a number of transcription factors, signaling proteins, translation factors and structural genes like transporters, multidrug resistance proteins, antiporters, chaperons, aquaporins etc. The gene expression levels and ratio of up/down-regulated genes was greater in tolerant plants. Translation related genes remained stable or showed slightly higher expression in tolerant plants under salinity stress. Further analyses of sequenced data and the annotations for gene ontology and pathways indicated that soybean adapts to salt stress through ABA biosynthesis and regulation of translation and signal transduction of structural genes. Manipulation of these pathways may mitigate the effect of salt stress thus enhancing salt tolerance.